Exploring the Relationship among Organizational Citizenship Behavior, Psychological Empowerment and Turnover Intensions with the Mediating Role of Affective Commitment - Iftikhar, Mehwish; Shahid, Muhammad Umer; Shahab, Muhammad Hamza; Mobeen, Mehvish; Qureshi, Muhammad Imran (International Review of Management and Marketing, 2016)
The paper aims to clarify the relationship between organizational citizenship behavior, psychological empowerment, affective commitment and turnover intensions along with mediating effects of variables. Main purpose of the study is to analyze the organizational citizenship behavior on the basis of five dimensions altruisem, courtesy, sportsmanship, civic virtue and conscientiousness and finding how OCB and psychological empowerment influence the affective commitment and turnover intensions of workers directly and indirectly. The paper opted for a causal study using the standardized questionnaire approach. Data set of 410 respondents, employees representing middle level management belonging to Hattar industry was studied. Analysis was conducted by application of SEM to explore the direct and indirect relationship among the constructs. The paper provides empirical insights about how variables influence each other and finally concluded that OCB with its five dimensions and psychological empowerment, both affect affective commitment positively in a respective manner while both the variables have negative impact on turnover intensions of employees. Research also resulted that Affective commitment acts as a mediating variable between OCB and Turnover intensions as well as psychological empowerment and turnover intensions of industry middle management workers. Keywords: Organization citizenship behavior, psychological empowerment, affective commitment, turnover intensions JEL Classifications: J10, M10